Tan (F(?)/2)-Expansion Method for Traveling Wave Solutions of the Variant Bussinesq Equations - İnan, İbrahim Enam (My University, 2017)
In this paper, we implemented a tan (F(?)/2)-expansion method for the traveling wave solutions of the variant Bussinesq equations.We have hyperbolic function solution, trigonometric function solution, exponential solution and rational solution for this equation.Recently, this method has been studied for obtaining traveling wave solutions of nonlinear partial differential equations by sciences.
Keywords: Fizik; Uygulamalı; Matematik; Fizik; Matematik; Fizik; Partiküller ve Alanlar